ACCURACY OF CYTOPATHOLOGY IN DIAGNOSIS THYROID NEOPLASMS: A CORRELATION STUDY WITH HISTOPATHOLOGICAL OUTCOMES IN SINDH, PAKISTAN (The Research of Medical Science Review, 2025)
Objectives: Thyroid neoplasms found serious issues mostly in females, for the sac of treatment un-necessary practice of Thyroidectomy or lobectomy carried out in hospitals, which can be reduce by proper treatment by evaluating cytological diagnosis and correlate with histopathology of Thyroid Neoplasms. Method: The 151 patients studies within 12 months, at Tertiary care hospitals of Jamshoro, Sindh, Pakistan. During study Different parameters like age, gender, hormonal analysis, along with cytological and Histopathological correlation were observed. Results: The findings shows higher frequency of female 134 (88.7%), while male were 17 (11.3%). The mean age and std 33.67 ±10.727 was observed. The hormonal results show mean & std of (T3)1.49 ± 0.619, (T4) 8.176 ± 3.512, while in (TSH) 3.291 ± 8.874. The histopathological findings and the biochemical analysis showed a negligible connection (p =.155) while The cytopathological results revealed 93.4% cases were benign,probable malignancy of 3.3%, follicular lesion or atypia of unknown significance were 2.6%, and Only 0.7%, diagnosed as a cystic swelling. The Histopathological diagnosis clarify that majority of (109 cases) were benign, 16 cases of benign nodular hyperplasia with lymphocytic thyroiditis, and 15 cases diagnosed as papillary carcinoma of the thyroid. Additionally, there were 8 cases of Hashimoto's thyroiditis, while follicular carcinoma was diagnosed in 3 cases. The results show a significant correlation (p = .001) between the Histopathological findings and FNAC results. The majority of the 141 cases—109 were benign, 8 were Hashimoto's thyroiditis, and 15 were benign nodular hyperplasia with lymphocytic thyroiditis. Furthermore, only two cases of follicular carcinoma and seven cases of papillary thyroid cancer were found. Conclusions: The results conclude that with accuracy of cytopathology can resolve problem of benign thyroid neoplasms which can be treated via medication, in case of malignant tumor lobectomies or thyroidectomies may be performed which treated through chemotherapy or radiation.